Midodrine as an Adjuvant to Intravenous Vasopressor Agents in Adults With Resolving Shock: Systematic Review and Meta-Analysis. (November 2020) - Hammond, Drayton A.; Smith, Melanie N.; Peksa, Gary D.; Trivedi, Abhaya P.; Balk, Robert A.; Menich, Bryan E.
Purpose: To evaluate the effects of midodrine in addition to intravenous vasopressor therapy on outcomes in adults recovering from shock. Materials and Methods: PubMed, Scopus, Clinicaltrials.gov, and published abstracts were searched from inception to November 2018 for studies comparing outcomes in shock after midodrine initiation versus no midodrine. Results: Three studies with 2533 patients were included. Patients in whom midodrine was added to intravenous vasopressor therapy compared to intravenous vasopressor therapy alone experienced similar intensive care unit (ICU; mean difference [MD]: 1.38 days, 95% confidence interval [CI]: −3.48 to 6.23, I 2 = 93%) and hospital lengths of stay (MD: 4.37 days, 95% CI: −3.45 to 12.19, I 2 = 93%) and intravenous vasopressor duration after midodrine initiation (MD: 7.28 days, 95% CI: −0.86 to 15.41, I 2 = 97%). Mortality was similar between groups (odds ratio: 0.74, 95% CI: 0.44-1.27, I 2 = 65%). Qualitative assessment of reporting biases revealed minimal location bias, moderate selective outcome reporting bias, no selective analysis reporting bias, and no conflict of interest bias. Conclusions: Midodrine had no effect on ICU or hospital length of stay. These results were highly susceptible to the study heterogeneity and availability. Future investigation into standardized initiation of midodrine at an adequate dosage with an expedited titration strategy is needed in order to assess the utility of this strategy in shock management.